Frequency of MTHFR GENE C677T Polymorphism for Non-Syndromic Autism Spectrum Disorder Patients - Bremmy Laksono; Ani Melani Maskoen; Tri Indah Winarni; Syarief Taufik; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2015)
Background: The folate metabolism is a pathway that may involve in the non-syndromic Autism Spectrum Disorder (ASD). Methylenetetrahydrofolate reductase enzyme has a key role in folate metabolism. The C677T polymorphism of MTHFR gene could reduce the effectiveness of the enzyme.Objectives: To evaluate the frequency of MTHFR geneC677T polymorphism for non-syndromic ASD patients.Method: Thirty-four DNA samples were taken from each group. PCR mixture was consisted of 1µL DNA, 2.5µL PCR buffer, 0.5µL dNTP, 1.5µL MgCL2, 0.125µLTaqenzyme, 0.5µLofforwardandreverseprimerandaquabidesttoreach a volume of 25 µL. The PCR profiles were initiation 95ºC for 5 min, denaturation 94ºC for 1min, annealing 55ºCfor 45 seconds, and elongation 72ºC for30 seconds. The cycles were done in 35 times an dfinal elongation was at 72ºC for 5min. The PCR product was 198bp, and then digested by the Hinfl enzyme for 16hours at 37°C, and visualized using2%agarosegeland then electrophoresed for 30 minutes at 100 volts.Result: Non-syndromic ASD samples showed none had homozygote mutant type (677TT), 3 (8.8%) samples had heterozygote (677CT)and 31 (91.2%) samples had wild type (677CC). Meanwhile, normal control showed only 1 (2.9%)sample had homozygote mutant type(677TT), 9 (26.5%) samples had heterozygote (677CT)and 24 (70.6%) samples had  wild type (677CC).Conclusion: The frequency of MTHFR geneC677T polymorphism in patients with non-syndromic ASD and controls are not significantly different.